Weight-based victimization, eating behaviors, and weight-related health in Sexual and Gender Minority Adolescents. (1st October 2019) - Himmelstein, Mary S.; Puhl, Rebecca M.; Watson, Ryan J.
Abstract: Weight-based victimization (WBV) is a common form of bullying associated with maladaptive eating, and poor weight-related health. Although sexual and gender minority (SGM) youth experience a number of eating and weight-related health disparities, the link between WBV and these outcomes has not been investigated in this vulnerable population. Data came from the LGBTQ Teen Study, a national survey of SGM adolescents. Participants provided data to assess body mass index (BMI), WBV, sexual identity, gender identity, dieting, binge eating, eating to cope with stress, weight control behaviors, exercise, and stress ( N = 9679). The sample was 66% White, with a mean age of 15.6 years; 58.5% had healthy weight, and 37.2% had overweight or obesity. Over half of participants reported WBV from family members and peers. WBV from family members was associated with maladaptive eating (i.e., binge-eating, unhealthy weight-control behaviors), dieting, and poor weight-related health (i.e., stress, exercise avoidance, less physical activity and poorer sleep); relationships remained significant after accounting for participants' age, BMI percentile for age and sex, race, gender identity, and sexual identity. Higher frequency of WBV at school, but not history of peer weight-based victimization, was associated with more maladaptive eating, dieting, and poorer weight-related health on all outcomes except physical activity. This is the first large-scale study that examined links between WBV, maladaptive eating behaviors, and weight-related health in SGM adolescents. These results suggest the need for increased awareness that WBV may play a role in maladaptive eating, and weight-related health of SGM youth, and may contribute to both elevated levels of eating disorders and obesity in this population.